Individualised training enhances initial acceleration performance in elite sprinters: a novel framework to support exercise selection - Klein, J.; Oeppert, T. J.; Braunstein, B.; Schapschröer, M. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: The 100 m sprint is broadly distinguished into the initial and pick-up acceleration, maximum speed and negative acceleration phases [3] with athlete`s performance resulting from the interaction of the subsequent sections. The acceleration phase is considered to be a key component of the race [2]. It is well established that acceleration performance is primarily determined by the athlete`s ability to generate a high ratio of forces (RF), which is highly dependent on technical components [4]. Although these characteristics seem well understood, there are currently no procedures that allow practitioners to tailor individual exercise selection to precisely target and optimize the underlying kinematic parameters. METHODS: Spatiotemporal variables and shin-roll kinematic behaviour [1] were obtained from 15 male (100 m-PR: 10.11-11.36 s) and 13 femlae (100 m-PR: 11.19-12.49 s) national to elite level sprinters. As a measure of initial acceleration performance V/T ratio (instantaneous velocity at 10 m divided by 10 m time) was calculated. In addition, biomotor capacity was assessed using countermovement and drop jumps. These metrics have been merged into individual profiles to provide insight into athlete`s strengths and weaknesses. Based on this, each athlete was assigned six profile-specific drills to refine sprint mechanics and assist in feeling acceleration-specific muscle activation. The individualised interventions were allocated to fifteen athletes (INT) and incorporated into the warm-up routine over a 4-week period (2x/w). The remainder of the participants (n=13) were included as a control group (CON) and maintained their group-based training regimen. Statistical inference for intervention response was conducted using stratified 2000 bootstrap resamples (and 95% bias-corrected and accelerated confidence intervals). The effect of group (INT vs CON) on V/T ratio was estimated using a linear regression model. RESULTS: Initial acceleration performance of participants who received a technical intervention improved significantly from pre- to post-intervention (mean change=.081, 95% CI [.031, .139], p=.003) and differed significantly from the observed change of CON group (mean change = -.093, 95% CI [-.173, -.03], p=.012). Increases in performance of the INT group were accompanied by changes in whole-body kinematic strategies, that were significantly greater than those of the CON group (p